2020
DOI: 10.1108/ijpcc-09-2020-0146
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 prediction and symptom analysis using wearable sensors and IoT

Abstract: Purpose The purpose of the research work is to focus on the deployment of wearable sensors in addressing symptom Analysis in the Internet of Things (IoT) environment to reduce human interaction in this epidemic circumstances. Design/methodology/approach COVID-19 pandemic has distracted the world into an unaccustomed situation in the recent past. The pandemic has pulled us toward data harnessing and focused on the digital framework to monitor the COVID-19 cases seriously, as there is an urge to detect the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Temperature Sensor: Thermostats are equipped with sensors when it comes to the human body thermometer and the robot skin temperature sensor, temperature sensors are commonly used. A COVID-19 sensor may be used to measure the temperature of a human body utilising LM 35, SMT 160-30, and DS 1820 [15].…”
Section: Prototype Design Modelmentioning
confidence: 99%
“…Temperature Sensor: Thermostats are equipped with sensors when it comes to the human body thermometer and the robot skin temperature sensor, temperature sensors are commonly used. A COVID-19 sensor may be used to measure the temperature of a human body utilising LM 35, SMT 160-30, and DS 1820 [15].…”
Section: Prototype Design Modelmentioning
confidence: 99%
“…• Wearable Medical Sensors (WMS): A WMS based solution called EasyBand [48] has recently been proposed to restrict the growth of new positive cases by tracking autocontact and supporting critical social distancing. In an other recent work [49,50], the authors proposed a solution called CovidDeep which uses commercial WMSs for the detection of the COVID-19 virus. Similarly, the authors of [51] developed an application that gathers self-reported symptoms as well as smartwatch and activity tracker data in order to differentiate between COVID-19 negative and positive cases in symptomatic persons.…”
mentioning
confidence: 99%